Vous êtes sur la page 1sur 32

3

3.1

31

3

.

...................................................................................................3
31........................................................................

3.1

3.1.1 32
3.1.2 36
3.1.3

32

39

3.2 : 41
3.2.1
3.2.2
3.2.3
3.2.4

41

47
48

54

3.3
3.3.1
3.3.2
3.3.3 65

61

61
64

Basic Counting Principals

3.1

32

3.1.1

The Product Principal

X W
Y Z 1 W
X

1
r1 r2 r3 4
(1) : s1 ) t1. (2 s1 ) t2. (3 s2 )t1. (4
s2 .t2 12 X .W
X W T
:

) T1 X (Y 3 : r1 r2 r

.3

) T2 Y (Z : s1 .s2
) T3 Z (W : t1 .t2

. T
T1 T2 T3
3 2 2 = 12


} { r1, r2, r3 } { s1, s2 } { t1, t2


T n :
c1
c2

.cn

T

33

c1 c2 K cn

100 999
3
.

: . 9
}{8,9, ,1,2,3

9
: 10

9
10
: 10

9
10
10
100 999
10 10 = 900 9

100 999 :
) (



9
.

9

9

34

3.1

9
9
8
:

9 9 8 = 648
9
9
8
648 3 ) .
(987102103104
} .{0,2,4,6,8
9 } {1,2,3,4,5,6,7,8,9
10 } {0,1,2,3,4,5,6,7,8,9
5 }{0,2,4,6,8

9 10 5 = 450
9
10
5
450 100 (998100102104) .999
} {2,4,6,8 4 .
4 ) 0
( . 3
.

4 4 3 = 48
4
4
3
48 3 204206208) .
(862864

: }9){1,2,3,4,5,6,7,8,9(
9
.
{1,3,5,7,9} 5
4 3
.
) (.

.{1,3,5,7,9} 5

5
8

8
5
8:

35

3
3.1.2


The Sum Principal

8 8 5 = 320
8
8
5
320 3 103105107) .
(987



17
666
:
.

10
17:
= 101010171717

10 10 10 17 17 17
4913000
4913000.
666

17 17 17 111171717 = 4913
4913.

X
W .2

36

3.1

4
Y Z .
X W Y 32 = 6
Z 22 = 4
10 = 4 + 6
X
W Y Z
.


T T1 T2 Tn

c1 + c2 + K + cn
c1 T1 c2 T2 cn
.Tn

4 5
7 .





.
.
:
:1 4
:2 5
:3 7.

5 7 = 140 4

16 = 7 + 5 + 4
.
:

37

5
. 4
5

5 = 20 4


7 = 28 4

7 = 35 5

73 = 35 + 28 + 20

100 :999

2
.
.320

: 0 0
.
:0 } {0
9
8:

9 8 1 = 72
8
9
1
:0 4{2,4,6,8}
8
7:

8 8 4 = 256
8
8
4
3
328 = 256 + 72

38

3.1

3.1.3

The InclusionExclusion Principal

10 .
050 0 9

.

9 8 7 6 5 4 3 2 1 0

A ) ( c( A ) = 10
B ) ( c( A ) = 17

A A A B B B

c( A A A B B B ) = 10 10 10 17 17 17
= 4,913, 000

3.2

39


89 2 01
) aa00001 aa00000
( .


: A
: B 89 2 01

A A B B B B B

c( A A B B B B B ) = 26 26 10 10 10 10 10
= 67,600, 000



}A A { 0} { 0} { 0} { 0} { 0

c( A A { 0} { 0} { 0} { 0} { 0} ) = 26 26 1 1 1 1 1

= 676
67,600, 000 - 676 = 67,599, 324
67,600, 000 - 676 = 67,599, 324

Counting Models: Permutations and Combinations

3.1

40

3.2.1

Permutations

)
( .

3

1234

.
.
n !n
0! = 1

n 1 n

n ! = n (n - 1) (n - 2) (n - 3) L 2 1

1! = 1
2! = 2 1 = 2
3! = 3 2 1 = 6
4! = 4 3 2 1 = 24
5! = 5 4 3 2 1 = 120
10! = 10 9 8 7 6 5 4 3 2 1 = 3, 628, 800

! )n ! = n ( n - 1

! 14 :

!14! = 14 13! = 14 13 12! = 14 13 12 11

.
!10! 10 9 8 7
=
= 720
!7
!7

41

10
9

)= ( n + 2) ( n + 1
1
)n ( n + 1

! ( n + 2) ( n + 1) n

!n
! )( n - 1

! )( n + 1) n ( n - 1

! )( n + 2

!n

! )( n - 1
! )( n + 1

A n . A
. k
k .A
A n .A

A = {1,2,3} :

.A

A. 2

A
.
132
213
312
321

21
13
23
32

123
231
12
31

24

) P ( n, k k
n . :
P ( 4, 4) = 24 P ( 3,2) = 6 P ( 3, 3) = 6

3.1

42

11
) . P ( n, k


k n
!n
! )( n - k

= )P ( n, k ) = n ( n - 1) ( n - 2) K ( n - k + 1

k n
:1 .n
:2 .n 1
:3 .n 2

: k 1 )(
k . n - k - 1 = n - k + 1
k

)P ( n, k ) = n ( n - 1) ( n - 2) K ( n - k + 1

) P ( n, k k .n
n
) . P ( n, n

1
n
! P ( n, n ) = n ( n - 1) ( n - 2) L 2 1 = n


.

3 {
.
} 3
4
P ( 4, 3) = 4 3 2 = 24

43

15
14
13
12

32

.

n = 6
6! = 720

:
6 6 .
.

6! = 720

24 = !4


:






.
9 9
.

362,880 = !9

44

3.1

4 :
3 :
2 :

:1 .!3
:2 .!4
:3 .!3
:4 .!2

4! 3! 2! = 1728 !3

:1 .!8
:2 .!2

2! = 80640 !8
:
:1 .!7
:2 !2

2! = 10080 !7


282240 = 80640 362880
:

:
:1 9.
:2 6.
:3 .!7
.!967

282240 = 10080 + 272160

45

18
17
16
3.2.2


Permutations

With
Repetition

3 5 6
. .
3
}A = {2,5,7,8,9

3 .A
A
3 .A
5

5 5 = 125 5
.


k n . nk

m
m }
.
{1,2,3,4,5,6,7,8,9 . 9m

7 624
624
.
.

104 = 10000

3.1

46

19
3.2.3






Combinations
.

}A = {a,b,c,d
A .
A 3.


.
} {b,c
} {b,d
} {c,d

} {a,c,d } {b,c,d

} {a,d

} {a,c

} {a,b,d

} {a,b,c

} {a,b

A n . k A
k .A
n
) C ( n, k k k

)(

n.
) C ( n, k
:
C ( n, 0) = 1 0
. f
C ( n,1) = n 1 n

.n
C ( n, n ) = 1 n n
.
19
C ( 4,3) = 4 C ( 4,2) = 6
) . C ( n, k

47

20


k n
)n ( n - 1) ( n - 2) K ( n - k + 1
!k

!n
! ) k !( n - k

= ) C ( n, k
=

:1
:2

k ) C ( n, k
! k

) C ( n, k ) k ! = P ( n, k

) P ( n, k
= ) C ( n, k
!k

) P ( n, k ) = n ( n - 1) ( n - 2) K ( n - k + 1

)n ( n - 1) ( n - 2) K ( n - k + 1
!k

= ) C ( n, k

!n

! ) P ( n, k ) = ( n - k
!n
! )n - k

(! k

= ) C ( n, k

)C(n,k
C ( n,1) C ( n, n ) C ( 11,7) C ( 8,5) C ( 8, 3) :

8 7 6
= 56
3 2 1

= )C ( 8, 3

8 7 6 5 4
= 56
5 4 3 2 1

= )C ( 8,5

3.1

48

22
21
11 10 9 8 7 6 5
= 330
7 6 5 4 3 2 1
!n
!n
= )C ( n,1
=
=n
! )1!( n - 1) ! ( n - 1
!n
!n
!n
= ) C ( n, n
=
=
=1
! n !( n - n ) ! n !0! n

= )C ( 11,7



:

.
.
3 {
}

( 43) = 433212 = 4

}A = { 0,1,2, 3,K ,19,20

A 15
A 3

.
.
13 21

( 1521) = 21 1520141913181217111610159148137 126 511410392 18 7 = 54264

3
} { 0,2,K ,18,20 11 .

( 113) = 115104 392817 = 462

( 1521)
8
8
) ( 3 ). ( 5

49

23 24
2
n k k n
n

)( k ) = ( n- k

)k = n - ( n - k

!n
= ) C ( n, k
(
! )k ! n - k
!n
=
) = C ( n, n - k
! ) [ n - ( n - k ) ] !( n - k

.10
4

4
.
4 10 .

( 104) = 104 392817 = 210

( 93) = 938217 = 84

7 3 .

3
.
.
4 7
7 6 5 4
= 35
4 3 2 1

= )C ( 7,4

3.1

50

26
25

:1
:2

3 )C ( 7,3
)C ( 3,1

3

7 6 5 3
= 105
3 2 1 1

= )C ( 7,3) C ( 3,1

16 } {0,1
1 10
1 .
.
1 10 }
) {16 , ,1,2,3 .( 1

C ( 16,10) = 8008


.

1 10
0 6

= 8008

! )( 10 + 6

!10!6

B
3
A B .3
A B 6
.
3 9 . 9 A

51

28
27

3.2.4

) B ( 6
6Combinations

With 3
Repetition

C ( 9,6) = 84

11
4 3 3

A n . k
A

:

.

4
.
{ }
4 3.
:
4
3
3

4
4
3 3
3 3


15 .

:
x1
x2
x3

a.

x1 + x2 + x3 = 4

3.1

52

29
) ( x1, x2, x3 x2 x1
x3 .
4 + 0 + 0 = 4 ) ( 4,0, 0 4
1 + 3 + 0 = 4 ) ( 1, 3, 0 3

1 + 1 + 2 = 4 ) ( 1,1,2
.
) (
.

1
k .
x1 + x2 + K + xn = k

)C ( k - 1, n - 1

)( nk-- 11

k = 1+ 1+ K + 1

1 k . + k - 1
k n
n - 1 ) ( . k - 1

11
) 11 +1 = 11
8+1+1 (1+8+1+1 = 11
k = 11 n = 4
.
11

( 114-- 11) = ( 103 ) = 103 2918 = 120

C ( 11 - 1, 4 - 1) = C ( 10, 3) = 120

3
k .

53

30
x1 + x2 + K + xn = k

)( k+n-n-11) C ( k + n - 1,n - 1


x1 + x2 + K + xn = k

. xn 0 x2 0 x1 0
y1 - 1 = x1
y2 - 1 = x2
M
yn - 1 = xn

. yn 1 y2 1 y1 1
:
y1 - 1 + y2 - 1 + K + yn - 1 = k

y1 + y2 + K + yn = k + n

)C ( k + n - 1, n - 1

4
k n
). C ( k + n - 1, n - 1

) ( a,b,c, d,e
a + b + c + d + e = 100

e 1 d 1 c 1 b 41 a 35
a - 34 1
.
b - 40 1

3.1

54

31 32

a+ 34 = a
a= a - 34
b= b - 40 b+ 40 = b


a+ 34 + b+ 40 + c + d + e = 100

a+ b+ c + d + e = 26

C ( 25, 4) = 12650

100,000
7
100,000
.

x5x4x3x2x1

0 xi 9 i 1 .5 4
x5 = 0 .

x1 + x2 + x3 + x4 + x5 = 7

) 9 .(7
3
C ( 7 + 5 - 1,5 - 1) = C ( 11, 4) = 330

20
:

20
.
.
20 5
) (2
C ( 20 + 5 - 1,5 - 1) = C ( 24, 4) = 10626

55

33

5
x2 x1
.
x
10
x1 + x2 + K + x10 = 100
x10 5 x2 5 x1 5


k n .

.


: :

3.1

56

3.3


3.3.1

Permutations With
Specified Repetitions

Applications of Permutations and Combinations

nk k
n
.
.
"" {

57

34
} !6 .12
""
) ( .
{
} : 1
1 2 .2
.
STATISTICS

S1T1AT2I1S2T3I2CS3

10 !10
STATISTICS
X
} X = {STATISTICS, TSATISTICS, TASTISTICS,

} X = {S1T1AT2I1S2T3I2CS3, T1S1AT2I1S2T3I2CS3, T1AS1T2I1S2T3I2CS3 ,


S1T1AT2I1S2T3I2CS3 !10

X ) . c( X
:1
S1S2S3 .!3
:2
T1T2T3 .!3
:3
I
I
1 2 .!2
:4
) c( X
!c( X ) 3! 3! 2! = 10
!10
= 50, 400
!3! 3! 2

= ) c( X

3.1

58

36
35


r
n1
n2

M
. nr
! ) ( n1 + n2 + K + nr

! n1! n2! K nr

:
: .
.
1
3
1
2

!7
= 420
!1! 3! 1! 2

! )( 1 + 3 + 1 + 2

!1! 3! 1! 2

:
347734313

:
3 4
4 2
7 2
1 1

59

37 38
3.3.3
3.3.2

!9
= 3,780
!4! 2! 2! 1

! )( 4 + 2 + 2 + 1

!4! 2! 2! 1

The Binomial
More
on Counting
Theorem
Problems

}A = {1,2,3,4,5,6

10
A
1 2 3
4
10 :A
.
:1 6
:2 6

:10 .6
6 6 6 6 6 6 6 6 6 6

60,466,176 = 610
1223334444
!10
= 12,600
!1! 2! 3! 4

! )( 1 + 2 + 3 + 4

!1! 2! 3! 4


12

3.2 ) ( k k
n
n

3.1

60
n

)( k ) = ( n- k
) 0 k n .(2
.

1 k n

)( nk+1) = ( k- 1) + ( k- 1

A n + 1 a A .
.
n +1
( k ) k .A
: a
.a
k a k 1
n
a . ( k- 1) { a }
A k a
n
k { a } n ). ( k

n 0 :
, k = 0,1, K , n

)( k

)( 77

61

)( 55

)( 66

)( 76

)( 44
)( 65

)( 33
)( 54
)( 75

)( 22
)( 43
)( 46

)( 11
)( 23
)( 35
)( 74

)( 00
)( 21
)( 24
)( 63

)( 10
)( 31
)( 25
)( 73

)( 20
)( 14
)( 26

)( 30
)( 15
)( 72

)( 40
)( 16

)( 50
)( 71

)( 60

)( 70

1
1
1
1
1
1
1
1

2
3

4
5

1
3

6
10

15
21

1
1
4
10
20

35

1
5

15
35

1
6

21

1
7

:4
.

)( nk) = ( n-n k


. .
.

n
k = 0 k = n ) : ( x + y

)( nk

= ( x + y)0

1
x +y

= )( x + y

x2 + 2xy + y2

= ( x + y)2

x3 + 3x2y + 3xy2 + y3

= ( x + y)3

x4 + 4x3y + 6x2y2 + 4xy3 + y4

= ( x + y)4

( x + y ) 4

3.1

62
:

)( x + y) 4 = ( x + y) ( x + y) ( x + y) ( x + y





( x + y)4


x y n 0
n

( k ) xn- kyk

= ( x + y) n

k=0

) (

) (

) (

) (

= 0 xn + 1 xn- 1y + 2 xn- 2y2 + K + n yn

) (
k- 1
n- 1